FENOMENA TINDAK PIDANA KORUPSI DAN PERTANGGUNG JAWABAN PIDANA DI WILAYAH HUKUM KABUPATEN INDRAGIRI HILIR - Vivi Arfiani Siregar; Indra Mukhlis Adnan; Wandi Wandi; Muhsin Muhsin; Jamri Jamri; Nurhan Nurhan; Feni Puspita Sari; Muannif Ridwan (Bajang Institute, 2022)
Regional and village funds are one of the sources of village funding based on regional funds as regulated in Law Number 6 of 2014 concerning Villages. Anticipations that the corruption of regional and village funds in Indragiri Hilir Regency does not continue to develop depends on how the implementation of law enforcement itself not only involves natural humans but can also be easily found in corruption cases involving legal entities. Metode community service by direct means of sources of information that are adjusted to the results of observations, because this approach in community service is carried out using a field approach. Criminal liability in corruption cases is broader than the general criminal law because perpetrators in corruption crimes are still held accountable for their actions even though the perpetrator has died but are only limited to deprivation of confiscated goods.